HOW DOES SCARCITY PROMOTION ELEVATE CONSUMER AGGRESSIVITY: AN EXPERIMENTAL STUDY CONDUCTED ON STUDENTS - Manggarani, Cynthia Ayu; Patiro, Shine Pintor Siolemba; Hendrian, Hendrian; Astuti, Tri (Universitas Padjadjaran, 2021)
Marketers often apply the strategy of scarcity promotion to attract consumer attention to the company’s product. However, this strategy often increases consumer’s destructive, aggressive behaviors. A quantitative approach using the experimental method was thus conducted in this study to reveal the effect of advertisement exposure with scarcity promotion strategy on aggressive consumer response towards the product that the company offered. The results show that advertisements with a scarcity strategy expose one’s perception that other consumers are perceived as threats. This perception arises since the probability of getting the product they want will be decreased when others are running after the same product. Theoretically, this condition will elevate the tendency of aggressive consumer behavior when attaining the product. Three studies with multiple behavioral measurements conducted on STIE YKPN students show destructive responses to the scarcity promotion applied by the company